Evaluating the impact of commercial radio occultation data using the observation system simulation experiment tool for ionospheric electron density specification - Hughes, Joseph; Collett, Ian; Crowley, Geoff; Reynolds, Adam; Azeem, Irfan (Frontiers in Astronomy and Space Sciences, 2024)
Decision makers c1 c2 must often choose how many sensors to deploy, of what types, and in what locations to meet a given operational or scientific outcome. An Observing System Simulation Experiment (OSSE) is a numerical experiment which can provide critical decision support to these complex and expensive choices. An OSSE uses a 'truth model' or 'nature run' to simulate what an observation system would measure, and then passes these measurements to an assimilation model. Then, the output of the assimilation model is compared to the truth model to assess improvement and the impact of the observation system. Orion Space Solutions has developed the OSSE Tool (OSSET) to perform OSSEs for ionospheric electron density quickly and accurately.In this study, we use OSSET to predict the impact of adding commercial radio occultation Total Electron Content (TEC) data to an assimilation model. c3 We compare the OSSE's predictions to the real performance at a group of validation ionosondes and find good agreement. c4 We also demonstrate the global assessments that are possible with OSSET using the improvement in critical frequency specification as an example. From this, we find that commercial radio occultation data can improve the critical frequency specification by nearly 20% at high latitudes c5 which are not covered by COSMIC-2. The commercial satellites are in sun-syncronous orbits with constant local times, and this improvement is concentrated at these local times.